Decomposição aeróbia de Myriophyllum aquaticum (Vell.) Verdc. e caracterização limnológica na bacia hidrográfica do rio do Monjolinho (São Carlos, SP, Brasil) - Santos, Mariana Gonzaga dos (Universidade Federal de São Carlos, 2009)
The oxidative aerobic processes contribute with large amounts of nutrients in dissolved and particulate forms for the metabolism microbial water. In that context, this study described the oxygen consumption kinetics during the aerobic mineralization of Myriophyllum aquaticum and also evaluated the possible effects of nutrients addiction, the chemical composition and temperature on the decomposition. The aquatic macrophyte was collected in the coastal region of the Monjolinho reservoir (220 00' S and 47054' W; SP, Brazil). In the laboratory part of the plant fragments were subjected to leaching for extraction of the dissolved organic matter (DOM). In the laboratory, part of the plant fragments was subjected to leaching to extract the particulate fraction (POM). The mineralization chambers were set up (n = 96) with different N and P concentrations, entire detritus or lignocellulosic matrix (i.e. fibers) in two phenological stages (senescent or green) under two temperature (16 and 25 ºC), totaling 32 treatments. The concentrations of dissolved oxygen (DO) were determined periodically in the chambers for 80 days. The results were adjusted to a kinetic model of first-order. Different concentrations of N and P did not interfere in the microbial metabolism when the experiments with full detritus and lignocellulosic matrix were analyzed separately. Moreover, in experiments that include the mineralization of macrophytes under natural conditions (with reservoir water), was favoring the mineralization rather than immobilization. However, the independent analysis of the concentrations of N and P showed that the same condition of temperature and type of fragment (green or senescent), the kD was approximately 2 times greater in treatments with full detritus for those with only lignocellulosic matrix, which showed higher C: P and smaller quantities of lignin in their original chemical composition. The Q10 has shown similarities between the treatments, regardless of chemical composition (entire or fibers), but differences in relation to the plant phenological stage (ranging from 1.75 to 2.06). Regarding the stoichiometry O/N was an expense of greater oxygen for nitrification in treatments with full litter (mean = 1%) compared to treatment with lignocellulosic matrix (mean = 0.6%). The quality of detritus was the most important variable in the mineralization of macrophytes the temperature has served as a secondary factor.
Keywords: Ecologia aquática; Myriophyllum aquaticum; Decomposição; Composição química; Monjolinho, Rio, Bacia (SP); Caracterização limnológica; CIENCIAS BIOLOGICAS::ECOLOGIA